PENGARUH KARAKTERISTIK DEMOGRAFIS (USIA, GENDER,PENDIDIKAN), MASA KERJA DAN KEPUASAN GAJI TERHADAP KOMITMEN AFEKTIF (Studi Pada Tenaga Paramedik Non-PNS RSUD Kota Semarang) - Hutagalung, Simson; Perdhana, Mirwan Surya (Faculty of Economics and Business Diponegoro University, 2016)
The purpose of this research is to extend previous research on employee commitment to their organization within with the measurability and the fitness of the tested and reliable employee commitment scale items in a non-western culture within focus to investigate the effect of demographic characteristic (age, gender, education), tenure and pay satisfaction on affective commitment based background of the phenomena that occur in the commitment of contractÂ paramedical employees at the General Hospital of Semarang.This research was conducted at the General Hospital of the city Â with A quantitative approachment.The data collection using five-point Likert scaled questionnaire administered to 75 contractÂ paramedical employees at the General Hospital of Semarang.The results indicates that there are no significant effect between both demographic characteristic (age, gender, education) and tenure on affective commitment.Conversely, the result indicate there is a positive significant correlation between pay satisfaction towards affective commitment at the General Hospital of Semarang.